2021
DOI: 10.1007/978-3-030-74608-7_24
|View full text |Cite
|
Sign up to set email alerts
|

A Staggered Seat is Beneficial for the Flying V Aircraft

Abstract: Staggered seats might be a solution for a V-shaped aircraft (the Flying V). The cabin longitudinal axis of this airplane has a 26°angle with respect to the direction of flight. When seats are positioned in the direction of flight, they consequently have an angle to the cabin and become staggered. It is unknown whether the comfort of this staggered seat is appreciated. In this study, 117 participants tested the comfort and the privacy experience in this staggered seat compared with a regular aircraft seat. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…The results of such analysis could be explained by embedding a discomfort triggered adjustment (DTA) process in existing comfort models to address the cycle of discomfort development, the trigger, and the friction between movement desire and the practical constraints until the joy of comfort [68]. Some studies have found that staggered seats were significantly better in terms of comfort and privacy based on short-term evaluations [69,70]. In summary, research on aircraft seats is mainly carried out by means of experimental simulations, which are costly, and the object of their study is mainly the comfort of the seats.…”
Section: Transportation Vehicle Seatsmentioning
confidence: 99%
“…The results of such analysis could be explained by embedding a discomfort triggered adjustment (DTA) process in existing comfort models to address the cycle of discomfort development, the trigger, and the friction between movement desire and the practical constraints until the joy of comfort [68]. Some studies have found that staggered seats were significantly better in terms of comfort and privacy based on short-term evaluations [69,70]. In summary, research on aircraft seats is mainly carried out by means of experimental simulations, which are costly, and the object of their study is mainly the comfort of the seats.…”
Section: Transportation Vehicle Seatsmentioning
confidence: 99%
“…This led to the idea of a new design called "staggered seats" which are designed for more leg room space and individual arm rest making more shoulder-to-shoulder space between passengers. Staggered seats are also placed at an angle with respect to the direction of flight which makes the seats not to fall in a single line but in an angled row [16].…”
Section: Fig 2 Multi User Co-located Collaborative and Interactive Pl...mentioning
confidence: 99%